Страганиассус (Straganiassus) — новый род цикадок подсемейства Jassinae с Дальнего Востока - Ануфриев, Г.А. (Вестник зоологии, 1971)
The genus Straganiassus gen. n. described for Stragania matsumurai Mete , differs from the genus Stragania S t a 1. with which it was confused, in the absence of
break in submarginal vein of fore-wings near the internal apical cell, as a result of which
this cell is completely separated from the appendage. From paleoarctic species of the
subfamily Jassinae (Jassus F a b г., Batrachomorphus L e w.) Straganiassus differs by
a shorter and higher genital segment of a male and by the absence of an appendage in
the anal tube and pygophore processes.